Interventions to increase adherence to micronutrient supplementation during pregnancy: a protocol for a systematic review. Issue 1 (13th February 2020) - Gomes, Filomena; Bergeron, Gilles; Bourassa, Megan W.; Dallmann, Diana; Golan, Jenna; Hurley, Kristen M.; King, Shannon E.; da Silva, Ana Carolina Feldenheimer; Mehta, Saurabh
Abstract: Micronutrient supplementation during pregnancy has been shown to be a cost‐effective method to reduce the risk of adverse pregnancy and birth outcomes. However, one of the main barriers to the successful implementation of a micronutrient supplementation program in pregnancy is poor adherence. Our review will assess the effectiveness of interventions designed to increase adherence to micronutrient supplements in pregnancy. Following the Cochrane Collaboration Methodology, we will start by conducting the literature searches on Medline (via PubMed), Embase, Scopus, Web of Science, and Cochrane Library, in addition to sources of gray literature, to retrieve all the available relevant studies. We will include randomized controlled trials and nonrandomized studies with a control group, where participants are pregnant women taking any micronutrient supplements in the context of antenatal care globally. We will include studies with targeted interventions designed to improve adherence to micronutrient supplementation in pregnant women compared with (1) usual care or no intervention or (2) other targeted micronutrient adherence intervention. Abstract selection, data extraction, and risk of bias assessment (according to the type of studies) will be conducted by two independent reviewers. The pooled results will be reported using the standardized mean differences for continuous data, and odds ratio or risk ratio for dichotomous data. We will assess sources of heterogeneity and publication bias. By following this protocol, we will systematically assess and synthesize the existing evidence about interventions designed to increase adherence to micronutrient supplementation in pregnant women. Understanding which strategies are more effective to increase the consumption of micronutrient supplements during this critical stage of life will have significant implications for clinicians and policymakers involved in the delivery of prenatal micronutrient supplementation interventions.